Online Literary Text Usage on the Students’ Reading Comprehension - Permadi, Rudi (Universitas PGRI Adi Buana Surabaya, 2019)
Recently, the upcoming era, namely industry revolution 4.0 becomes trend topic and big issues. It has many roles in aspects of life. It can be recognized in teaching and learning process also. English practitioners, both teachers and students, should involve and master technology to improve their English capability or skills as the consequently. The research plays technology as a message of industry revolution 4.0 to encounter English teaching problem. The objective of the research is to find the effect of online literary text usage on the students’ reading comprehension. The research methodology is using experiment with a factorial design. Data collection is obtained by examining reading comprehension test. One paired sample t-test acts to analyze the data. The number of sample is 40 students of 50 population number at Islamic studies program Sekolah Tinggi Agama Islam academic year 2017/2018. Random sampling works as technique of taking the sample. Data calculation and analysis shows that Asymp. Sig. (2-tailed) =0.000 less than Asymp. Sig. (2-tailed) < 0.05 explaining that H0 is rejected. It means that there is a significant effect of online literary text on the students’ reading comprehension. Seeing the research result, it is suggested to English practitioners, both teachers and students, keep in touch online literary text to improve the students’ reading comprehension